The strategy of a book publisher during the pandemic: A case study from Deepublish - Ayu Dwi Utami; Aruming Sekar Sukrani Candra Dewi; Danang Yudhiantoro (Universitas Sebelas Maret, 2021)
This article provides a case study related to the strategy of the Deepublish publishing company in dealing with the Covid 19 Pandemic crisis that has entered Indonesia since March 2, 2020. We provide an explanation regarding the impact of the pandemic on the publishing world. This article uses a descriptive case study and a literature review using data from the Deepublish company. We found the company's marketing strategy, namely B2C, which was initially less superior than competing companies, actually became an advantage for Deepublish. The application of the flywheel marketing concept, adding title assets, and optimizing distribution channels encourage companies to continue to exist and increase company turnover. The results of this study are expected to be a benchmark for other publishing companies.